A phase-retrieval toolbox for X-ray holography and tomography - Lohse, Leon M. (J Synchrotron Radiat, 2020)
Propagation-based phase-contrast X-ray imaging is by now a well established imaging technique, which – as a full-field technique – is particularly useful for tomography applications. Since it can be implemented with synchrotron radiation and at laboratory micro-focus sources, it covers a wide range of applications. A limiting factor in its development has been the phase-retrieval step, which was often performed using methods with a limited regime of applicability, typically based on linearization. In this work, a much larger set of algorithms, which covers a wide range of cases (experimental parameters, objects and constraints), is compiled into a single toolbox – the HoloTomoToolbox – which is made publicly available. Importantly, the unified structure of the implemented phase-retrieval functions facilitates their use and performance test on different experimental data.